The Analysis of Screws Spacing Effect On The Flexural Strength Of Laminated Wood Beams From Pine Pallets Waste - Arnandha, Yudhi; Pandhini, Kadarosi Dyah; Murtopo, Ali (Universitas Negeri Yogyakarta, 2023)
Pine pallets are often used to design the interior of houses, as opposed to pine waste, which is underutilized due to its reduced strength and limited size. Therefore, this research aims to optimize the use of pine pallet waste by making laminated beams using screw joints and determining the effect of screw spacing on the strong bending of laminated beams. Flexural strength tests of laminated wood beams measuring 5 cm x 5 cm x 76 cm with varying screw spacing of 4 cm, 8 cm, 12 cm, and 16 were used to conduct this research. This is in addition to screw length, head, and body diameters of 5 cm, 8 mm, and 4 mm, respectively. Strong bending testing was carried out at the Structural Laboratory of the Department of Civil Engineering, Faculty of Engineering, Tidar University, Magelang. The test results of consecutive Modulus of Rupture (MOR) had average values of 20.996 MPa, 23.067 MPa, 20.207 MPa, 19.292 MPa. and Modulus of Elasticity (MOE) of 1,352.68 MPa, 1,449.35 MPa, 1,146.76 MPa, and 1,128.90 MPa. The result showed that the use of varying screw spacing has no significant effect on the flexural strength of laminated beams. Furthermore, the laminated pine pallet waste with screws can be used as an alternative to pure wood by paying attention to the proper joint spacing.